Comparative study of single versus multiple gallstone disease in KGH, Visakhapatnam - Raja, C. Dharma Kishore; Keerthi, Dondapati; Kiran, Adikari Sai; Aravind, Gunti; Raja, Sreerama; Karthik, G. Manoj; Sreenija, Devarakonda; Kumar, Nelapati Kiran (International Surgery Journal, 2020)
Objective: To evaluate the differences in the presentation, their operative implications and difficulties of single stone versus multiple gall stone disease. Methods: This is a prospective study of a minimum of 60 patients with gall stone disease (Group 1-single, Group 2-multiple) from January 2019 to December 2019 in KGH, Visakhapatnam. Results: More common in females, 40-50 years symptoms and complications, TC count difficult cholecystectomies were more in multiple gall stone pts. Conclusion: Multiple gall stones have led to more severe symptoms and complications and difficult surgery. should be motivated for early surgery even in incidental finding and should not opt for conservative management.